Studies on the Mechanism of Interferon Action - Friedman, Robert M. (The Rockefeller University Press, 1970)
Interferon does not inactivate viruses or viral RNA. Virus growth is inhibited in interferon-treated cells, but apart from conferring resistance to virus growth, no other effect of interferon on cells has been definitely shown to take place. Interferon binds to cells even in the cold, but a period of incubation at 37°C is required for development of antiviral activity. Cytoplasmic uptake of interferon has not been unequivocally demonstrated. Studies with antimetabolites indicate that the antiviral action of interferon requires host RNA and protein synthesis. Experiments with 2-mercapto-1(β-4-pyridethyl) benzimidazole (MPB) suggest that an additional step is required between the binding and the synthesis of macromolecules. Interferon does not affect the adsorption, penetration, or uncoating of RNA or DNA viruses, but viral RNA synthesis is inhibited in cells infected with RNA viruses. The main action of interferon appears to be the inhibition of the translation of virus genetic information probably by inhibiting the initiation of virus protein synthesis.